Brief notes on the standing to act of the Tax Administration and Article 157 of the Tax Code - Bardales Castro, Percy Enrique (2021)
This document intends to address, at first, the legislative treatment that article 157 of the Tax Code has had over time, in relation to the possibility that the Tax Administration may challenge the resolutions issued by the Tax Court through the contentious-administrative process. On this basis, in a second stage, the normative scope of this matter will be analyzed based on the current text of article 157 of the Tax Code.